SIMBOLISME LITURGI EKARISTI DALAM GEREJA KATOLIK SEBUAH KONSEPSI DAN APLIKASI SIMBOL - Wardani, Laksmi Kusuma (Dimensi Interior, 2006)
Liturgy represents the experience of believing in God as well as the aesthetic experience containing elements of emotional rituals. It also possesses a creative goal, that is the formation of symbols, and the content symbolized is heading no other than towards reality, that is the presence of Christ the saviour. The religious experience in the ceremony of Eucharistic liturgy does not only act as an intellectual or philosophic experience, but also includes human feelings and actions. On the other hand, the Catholic Church building as God's house represents the sacred building loading aesthetic experiences, signs and symbols of heavenly nature that reflects the mystery and supremacy of God. The church service space applies the symbolic and sacred values through the supply of various religious service facilities, the use of symbols, and the materialization of space atmosphere in its zoning, walls, floors, ceilings, windows, furniture, decorations, colour, and others, capable of bringing the church people to the experience the reality celebrated in liturgy. Abstract in Bahasa Indonesia : Liturgi merupakan pengalaman keimanan dan sekaligus pengalaman estetis yang mengandung unsur ritual emosional, dan memiliki tujuan kreatif yaitu pembentukan simbol, dan isi yang disimbolkan tidak lain menuju ke arah realitas, yakni kehadiran Kristus yang menyelamatkan. Pengalaman religiusitas dalam upacara liturgi ekaristi tidak hanya sebagai pengalaman filosofis atau intelektual, tetapi juga melibatkan perasaan dan tindakan manusia. Sedangkan bangunan gereja katolik sebagai rumah Tuhan merupakan bangunan sakral yang memuat pengalaman estetik, memuat tanda dan lambang alam surgawi yang mencerminkan misteri Allah dan sifat keagungan Tuhan. Ruang ibadah gereja menerapkan nilai-nilai simbolik yang sakral melalui penyediaan berbagai fasilitas ibadah, penggunaan tanda, dan perwujudan suasana ruang, baik pada zoning, dinding, lantai, plafon, jendela, perabot, dekorasi, warna, dan lain-lain. Yang mampu membawa umat pada pengalaman realitas yang dirayakan dalam liturgi. Kata kunci: simbol, interior, gereja katolik.